Error Performance Analysis of Trellis Coded Modulation (TCM) in Various Wireless Channel Conditions - NASRI KELTOUM; Mourad Reggab (UNIVERSITE AMAR TELIDJI LAGHOUAT-FACULTE DE TECHNOLOGIE-DEPARTEMENT D’ELECTRONIQUE, 2025)
Reliable data transmission is a fundamental challenge in modern wireless communication systems, especially under adverse channel conditions such as noise and fading. Among various techniques developed to address this issue, Trellis Coded Modulation (TCM) stands out as an efficient approach that combines coding and modulation to enhance error performance without increasing bandwidth. This study explores the principle of TCM, its technical implementation, and its effectiveness across different wireless channel models. Trellis Coded Modulation (TCM) is a technique that enhances the reliability of data transmission by combining convolutional coding with modulation, without increasing the required bandwidth. By introducing redundancy and exploiting the structured transitions of a trellis diagram, TCM improves error correction capability, making it particularly effective in challenging wireless environments. Simulation studies reveal that TCM significantly reduces the Bit Error Rate (BER), especially in fading channels. The best performance is observed in AWGN channels, while in Rayleigh and Rician fading environments, TCM offers substantial robustness compared to uncoded systems. The TCM system integrates convolutional coding, which introduces controlled redundancy to aid error correction, and a Viterbi decoder, which efficiently estimates the most probable transmitted sequence by navigating the trellis structure. Two modulation schemes are utilized: • 8-PSK, used for uncoded reference scenarios. • 16-QAM, a higher-order modulation offering higher spectral efficiency but increased noise sensitivity, mitigated by TCM. Three wireless channel models are considered: • AWGN (Additive White Gaussian Noise): A baseline channel introducing random noise. • Rayleigh Fading: Models severe multipath conditions with no line of sight. • Rician Fading: Represents environments with a dominant direct path alongside multipath reflections. TCM demonstrates clear performance gains across all channel types. Its ability to reduce BER is especially noticeable in fading environments, making it a valuable solution for improving reliability in modern wireless communication systems.
Option : Réseaux et télécommunications